Ruscogenin Mainly Inhibits Nuclear Factor-κB but Not Akt and Mitogen-Activated Protein Kinase Signaling Pathways in Human Umbilical Vein Endothelial Cells - Jiaxi Song; Junping Kou; Yalin Huang; Boyang Yu (Elsevier, 2010)
Our previous results suggested that ruscogenin inhibited tumor necrosis factorα (TNF-α)-induced leukocyte adhesion, which correlated with its suppression of intercellular adhesion molecule-1 (ICAM-1) expression in endothelial cells. In the present studies, we further examined its effects on the main signaling pathways involved in upregulation of ICAM-1 induced by TNF-α in human umbilical vein endothelial cells (HUVECs). The results showed that ruscogenin significantly suppressed p65 phosphorylation, IκB-α phosphorylation and degradation, and inhibited IκB kinaseα (IKKα) and IKKβ activation induced by TNF-α. However, it exerted weak effects on TNF-α-induced phosphorylations of p38, JNK, ERK1/2, and Akt. Overall, our results indicated that downregulation of ICAM-1 expression by ruscogenin in HUVECs might be mediated by nuclear factor-κB (NF-κB), but not by mitogen-activated protein kinase (MAPK) and Akt signaling pathways. Keywords:: ruscogenin, nuclear factor-κB (NF-κB), mitogen-activated protein kinase (MAPK)